2019
DOI: 10.1002/app.48765
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity of waxes as model systems for polyethylene: Role of water

Abstract: Novel experimental and theoretical studies of the electrical conductivity of high‐purity dodecane, paraffin wax, and low‐density polyethylene (PE) are reported herein. The role of the charge density, water content, and phase changes in determining conductivity as the temperature increases from 25 to 65 °C, a temperature range relevant to applications of insulating materials, is determined. Low levels of absorbed water determine the measured conductivity for T < 50 °C and this can be explained by taking account… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…As such, DC conductivity values were first estimated from each data set by averaging the final 10 data points obtained ( σ DC1 ). Second, the time dependent conductivity, σ ( t ), data shown were fitted to a modified form of the Curie‐Von Schweidler law [22], which incordsporates a steady state, DC conductivity term, σ DC2 : σ ( t ) = σ D C 2 + a t b …”
Section: Resultsmentioning
confidence: 99%
“…As such, DC conductivity values were first estimated from each data set by averaging the final 10 data points obtained ( σ DC1 ). Second, the time dependent conductivity, σ ( t ), data shown were fitted to a modified form of the Curie‐Von Schweidler law [22], which incordsporates a steady state, DC conductivity term, σ DC2 : σ ( t ) = σ D C 2 + a t b …”
Section: Resultsmentioning
confidence: 99%
“…Although waste polyethylene wax and its blends have not been extensively studied in the literature, there are many studies regarding various other waxes and their blends with other material 4–7 . Paraffin wax has been used as model systems for polyethylene for studying electrical conductivity, and the conductivity of wax has been studied since 1932 8 . The blends of wax and polyethylene have drawn attention to themselves since they have many valuable properties such as lightweight, good processability, and low cost 9 .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Paraffin wax has been used as model systems for polyethylene for studying electrical conductivity, and the conductivity of wax has been studied since 1932. 8 The blends of wax and polyethylene have drawn attention to themselves since they have many valuable properties such as lightweight, good processability, and low cost. 9 The primary application of these blends is as phase change material (PCM).…”
Section: Introductionmentioning
confidence: 99%
“…In seeking to estimate a DC conductivity value from such data, a number of strategies are possible, such as averaging a number of current measurements obtained within the apparently steady‐state regime, or fitting the raw data to some suitable function. Recently, Hosier et al [48] contrasted these two approaches and reported that, for their systems, the use of the Curie von Schweidler law [49] modified by the addition of a time‐independent steady‐state DC conduction term led to more reliable DC conductivity values. As such, the same approach was used here, but, in this case, the results were found to fall within the uncertainties associated with direct current measurements.…”
Section: Ageing Morphology and Charge Transportmentioning
confidence: 99%